The Wesleys in Cornwall, 1743-1789: a record of their activities town by town - Rogal, Samuel J. (McFarland & Company, Inc., Publishers, 2015)
"In half-century of missionary work throughout England, Wales, Scotland and Ireland, brothers John and Charles Wesley found the southwestern county of Cornwall to be among their most serious theological and social challenges. The men were more interested in the bulk of their pocketbooks than the status of their souls. The clergy of the Church of England opposed the Wesleys and their itinerant preachers, encouraging Anglicans to disrupt the Wesleys' outdoor services and to attack and burn Methodist preaching houses. This book considers the mission with a close reading of the Wesleys writings, and covers the overall history of 18th-century British Methodism and its contribution to the religious and social history of the British Empire"--Provided by publisher